The first clusters of Middle East respiratory syndrome coronavirus in Oman: Time to act - Salah T. Al Awaidy; Ali Abdullah Al Maqbali; Iyad Omer; Suad Al Mukhaini; Mohammed Ali Al Risi; Majed Sultan Al Maqbali; Ali Al Reesi; Mujahid Al Busaidi; Fatma Hashim Al Hashmi; Talib Khamis Al Maqbali; Vidyanand Vaidya; Elham Said Ahmed Al Risi; et al. (Journal of Infection and Public Health, 2020)
Introduction: Middle East respiratory syndrome coronavirus (MERS-CoV), is an emerging infectious disease of growing global importance. This review describes the latest MERS-CoV clusters and the first cases of nosocomial transmission within health care facilities in Oman. We have highlighted lessons learned and proposed steps to prevent healthcare-associated infections. Methods: A descriptive analysis of MERS-CoV cases was conducted between January 23 and February 16, 2019. The data from officials and other published sources used. Results: Thirteen laboratory-confirmed cases of MERS-CoV were reported from three simultaneous clusters from two governorates without an epidemiological link between the clusters. Two clusters were reported from North Al Batinah Governorate, with nine cases (69%) and 1 cluster from South Ash Sharqiyah Governorate with four cases (31%). In total, four deaths were reported (case fatality rate 31%). Four cases (31%) reported were household contacts from the first cluster, 3 (23%) were nosocomial transmission in health care facilities (two for first and one from the second cluster) and 7 (54%) were community-acquired cases. Conclusions: The first local clusters of MERS-CoV reported with evidence suggestive of healthcare and household-associated transmission. Early diagnosis and strict implementation of infection control measures remain fundamental in preventing and managing MERS-CoV infection. Keywords: Middle East respiratory syndrome coronavirus, MERS, MERS-CoV, Healthcare associated transmission, Household-associated transmission, Nosocomial infection, Infection control, Oman